Kinetic analysis of Poultry Processing Dewatered Sludge (PPDS) Using Thermogravimetric Analysis (TGA) - Aniza, N. (EDP Sciences, 2014)
Kinetic analysis is one of the most important applications in thermal analysis study. In this work, the kinetic analysis of poultry processing dewatered sludge (PPDS) was conducted by using a Thermogravimetric Analysis (TGA) instrument. The kinetic parameters such as activation energy (E a) and correlation coefficient (R2) was determined. For this purpose, the non-isothermal thermogravimetric analysis was done in four different heating rates, Î²=5, 10, 15 and 20 K/min under oxygen atmosphere. The calculation of kinetic parameters adopted the Flynn-Wall-Ozawa (FWO) and Kissinger-Akihara-Sunose (KAS) model. The ranges of activation energy of the combustion of the PPDS were 11.81- 51.39 kJ/mol and 5.34- 42.63 kJ/mol respectively. Â© 2014 Owned by the authors, published by EDP Sciences.